Transformation of Cartoons as an Expression of Indian Politics in Contemporary Society: The Power of Political Cartoons in Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Political cartoons, for editorials in India can amuse, make us laugh but intends to provide social reflection on crucial facets of reality. This research a structure of analysis, which embraces the perceptual technique of ridicule and linguistic analytic agenda in the interior of the territory of serious communication study. The objective of the exploration is to recognize the lack of encouraging and openly outlined credentials during analysing constitutional caricatures as a key tool of communication. The objective also, influences the comprehension of political cartoons and the research by analysing the modern digital art and elements used in the cartoons which illustrate how Indian cartoonists have transformed by using digital tools that could be used possibly to introduce and be helpful for social and political changes in India. The paper underwrites to the study by posing comprehensive vision to the political cartoon’s categorization over strategy placing theory of media impact.